Language, Status Planning, And Political Stigma In Leila S. Chudori’s Namaku Alam - Made Eva Trisnadewi (Indonesian Journal of Foreign Language Studies, 2026)
This study aims to deeply analyze the role of language as an instrument of language planning in the formation and maintenance of political stigma against the descendants of political prisoners (tapol) during the New Order era, as reflected in Leila S. Chudori's novel Namaku Alam. While previous studies have explored the novel’s historical themes, there remains a significant research gap regarding how state-sponsored language planning specifically engineers the social marginalization of second-generation victims. This research offers a novel approach by integrating the framework of status planning—typically used in sociolinguistic policy studies—with literary critical discourse analysis to examine how linguistic policies dictate social hierarchy. The research data consist of excerpts from dialogue, narratives, and key terms in the novel related to political discrimination. The results show that the New Order regime successfully engineered social status through three main linguistic strategies: 1) Codification of Official Stigma: Through bureaucratic terms such as "clean environment" (bersih lingkungan) and "clean self" (bersih diri), which functioned as euphemisms to justify systematic surveillance and discrimination. 2) Construction of Binary Oppositions: Dividing society into ideological categories of "State" (good, high-status) versus "Traitor" (bad, low-status) through punitive phrases like "child of a traitor to the state" (anak pengkhianat negara). 3) Internalization of Stigma: The stigmatizing language was acquired by the wider community, including the social environment and peers, making discrimination a daily practice. Language does not merely reflect but actively plans social status, transforming the identity of the main character, Segara Alam, into a marginalized existence. This novel reflects the failure of authoritarian language planning in fostering social integration, instead creating segregation and trauma inherited through language. Keywords: Language Planning, Status Planning, Political Stigma, Namaku Alam